Retrospective Analysis of Outcomes after Anterior Cervical Discectomy and Fusion (ACDF) for Cervical Spine Disorders - Abhinav, Kumar; Rajan, Rajiv; Kumar, Kunal; Chaudhary, Abhishek (Journal of Neonatal Surgery, 2025)
Background: Cervical spine disorders, including disc herniation, spondylotic myelopathy, and radiculopathy, are common degenerative conditions that can significantly impair quality of life. Anterior Cervical Discectomy and Fusion (ACDF) is a widely performed surgical procedure aimed at relieving neural compression and stabilizing the cervical spine. This study aims to evaluate the clinical, functional, and radiological outcomes of ACDF in patients with cervical spine pathology. Methods: A retrospective observational study was conducted on 100 patients who underwent single- or multi-level ACDF. Data collected included demographic information, surgical details, clinical outcomes assessed using Visual Analog Scale (VAS) and Neck Disability Index (NDI), radiological fusion status, and postoperative complications. Statistical analysis was performed using paired t-tests and chi-square tests, with a significance threshold set at p<0.05. Results: The study population comprised 56 males and 44 females with a mean age of 49.3 years. The most frequently operated levels were C5-C6 (52%) and C6-C7 (29%). Single-level ACDF was performed in 71% of cases, while 29% underwent multi-level fusion. The mean operative time was 98 minutes, and the average hospital stay was 3.4 days. VAS scores improved significantly from 7.8 preoperatively to 2.1 postoperatively (p<0.001). NDI scores improved in 84% of patients, and neurological recovery was observed in 87%. Radiological fusion was achieved in 91% of patients at six-month follow-up. Complications included transient dysphagia (11%), wound infection (3%), pseudarthrosis (6%), and early adjacent segment disease (2%). Conclusion: ACDF is a safe and effective surgical approach for cervical spine disorders, providing significant symptom relief, functional recovery, and high fusion rates with a low incidence of complications.